A Convenient One-Pot Synthesis of N-Substituted 2-Aminoazole Derivatives - Yotphan, Sirilata; Beukeaw, Danupat; Reutrakul, Vichai (Synthesis, 2013)
A practical protocol for the one-pot synthesis of N-substituted 2-aminoazole derivatives is described, employing simple azole substrates, nitrogen nucleophiles, lithium tert-butoxide as the base, and iodine to mediate carbon–nitrogen bond formation. This method proceeds at room temperature under an air atmosphere using a normal benchtop set-up, or can be performed conveniently using microwave irradiation.
Keywords: N-substituted 2-aminoazoles; iodine; one-pot synthesis; benzoxazole; carbon–nitrogen bond formation